IMPORTANCE OF PSYCHOLOGICAL KNOWLEDGE IN LEARNING FOREIGN LANGUAGES - Qarshiboyeva, Dilfuza (Журнал Педагогики и психологии в современном образовании, 2022)
In this article it is given full information why psychological knowledge play more important role in learning second languages without taking into consideration age factor.In deed,Psycholinguistics has provided numerous theories that explain how a person acquires a language, produces and perceives both spoken and written language. The theories have been used in the field of language teaching. Some experts use them as the basic theories in developing language teaching methods. It is known as psycholinguistics approach. Psycholinguistic approach views learning as a cognitive individual process happening within the individual and then moves to the social dimension.